Bitcoin networks in international trade - Lim, Shian (2015)
This paper studies the impacts of Bitcoin networks in international trade and suggests the mechanisms through which the effects come into place. In this paper, we examine the networks effects promote trade by mitigating the informal barriers and the issue of whether the efficiency of the Bitcoin payment system would induce its users to trade more internationally. The study related to Bitcoin is still lacking, as data available is not very accessible and adequate, and the nature of price volatility leads people to make presumption that it is just a form of speculation. Gravity model approach is used in our regression. We found Bitcoin networks have significantly positive impacts on international trade. The aggregate effect is then further analyzed in accordance to industries to draw deeper insights. Given the findings, we could learn more about the effects of its community on international trade, as well as how the users are making use of Bitcoin, as a more efficient payment system.